1996
DOI: 10.1111/j.1460-9568.1996.tb01214.x
|View full text |Cite
|
Sign up to set email alerts
|

Less Segregated Processing of Visual Information in V2 than in V1 of the Monkey Visual Cortex

Abstract: To test the possibility of cross-talk between parallel pathways dealing with different aspects of visual information such as orientation, direction of motion and colour in cortical area V2, we quantitatively analysed visual responses of 121 V2 cells recorded from anaesthetized and paralysed macaques and compared them with those of 147 V1 cells. A selectivity index of visual responses was calculated for each neuron, which was then classified as selective or not to a particular attribute of visual stimuli. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 40 publications
6
48
0
3
Order By: Relevance
“…Hubel and Livingston (1987) concluded that it represents a specialized color system in the primate. At least 13 other reports have focused on the physiological characteristics of cells in different V2 stripe classes (DeYoe and Van Essen, 1985;Peterhans and von der Heydt, 1993;Levitt et al, 1994;Ts'o, 1995, 1999;Gegenfurtner et al, 1996;Tamura et al, 1996;Yoshioka and Dow, 1996;Kiper et al, 1997;Xiao et al, 1999Xiao et al, , 2003Ts'o et al, 2001;Moutoussis and Zeki, 2002;Shipp and Zeki, 2002). The verdict from these studies has been mixed, with some investigators confirming that colorselective cells are more prevalent in thin stripes, and others dissenting.…”
Section: Discussionmentioning
confidence: 78%
“…Hubel and Livingston (1987) concluded that it represents a specialized color system in the primate. At least 13 other reports have focused on the physiological characteristics of cells in different V2 stripe classes (DeYoe and Van Essen, 1985;Peterhans and von der Heydt, 1993;Levitt et al, 1994;Ts'o, 1995, 1999;Gegenfurtner et al, 1996;Tamura et al, 1996;Yoshioka and Dow, 1996;Kiper et al, 1997;Xiao et al, 1999Xiao et al, , 2003Ts'o et al, 2001;Moutoussis and Zeki, 2002;Shipp and Zeki, 2002). The verdict from these studies has been mixed, with some investigators confirming that colorselective cells are more prevalent in thin stripes, and others dissenting.…”
Section: Discussionmentioning
confidence: 78%
“…One candidate representing another line component is subthreshold excitatory interactions mediated by the long-range horizontal connections within area V2. Horizontal connections in the primary visual cortex are known to connect multiple cortical columns sharing the same orientation preference (Ts'o et al, 1986;Ts'o and Gilbert, 1988;Gilbert and Wiesel, 1989), but some V2 neurons having an orthogonal orientation preference show cross-correlation peaks near 0 msec, suggesting that horizontal connections may contribute to the formation of angle selectivity (Tamura et al, 1996). Complex integration beyond the CRFs has been observed in area V2 (von der Heydt and Peterhans, 1989;Bakin et al, 2000;Zhou et al, 2000).…”
Section: Neuronal Mechanisms For Extracting Angles In Area V2mentioning
confidence: 93%
“…Aynı çalışmada V1 lezyonunda görme keskinliği-nin azaldığı, V2 lezyonunda ise daha kompleks görsel ayırım testlerinin etkilendiği, bir diğer çalışmada V2 alanında birden fazla modaliteye yanıt veren hücre sayısının, V1 alanından daha fazla olduğu bulunmuş-tur. Bu bulgular, V2 alanının V1 alanına göre daha kompleks görsel işlemlerle ilişkili olduğunu göster-mektedir (19,27).…”
Section: Sekonder Görsel Alanlarunclassified
“…V2 alanında sitokrom oksidazla gösterilen ve VI'in farklı işlevsel bölgelerinden projeksiyon alan, farklı fonksiyonlarla ilişkili olduğu ileri sürülen açık, koyu kalın ve koyu ince çizgi bölgelerinde bulunan hücrelerin yanıt özellikleri birbirlerine benzerlikler göstermektedir, açık, ince ve kalın çizgiler birbiri ile bağlantılıdır (11,27,30).…”
Section: Dorsal Ve Ventral Kanallar M Ve P Kanallarının Kortikal Uzanunclassified
See 1 more Smart Citation